Mifepristone as a Potential Therapy to Reduce Angiogenesis and P-Glycoprotein Associated With Glioblastoma Resistance to Temozolomide - Llaguno-Munive, Monserrat; León-Zetina, Sebastián; Vazquez-Lopez, Inés; Ramos-Godinez, María del Pilar; Medina, Luis A.; Garcia-Lopez, Patricia (Frontiers in Oncology, 2020)
Glioblastoma, the most common primary central nervous system tumour, is characterised by extensive vascular neoformation and an area of necrosis generated by rapid proliferation. The standard treatment for this type of tumour is surgery followed by chemotherapy based on temozolomide and radiotherapy, resulting in poor patient survival. Glioblastoma is known for strong resistance to treatment, frequent recurrence and rapid progression. The aim of this study was to evaluate whether mifepristone, an antihormonal agent, can enhance the effect of temozolomide on C6 glioma cells orthotopically implanted in Wistar rats. The levels of the vascular endothelial growth factor (VEGF) and P-glycoprotein (P-gp) were examined, the former a promoter of angiogenesis that facilitates proliferation, and the latter an efflux pump transporter linked to drug resistance. After a 3-wk treatment, the mifepristone/temozolomide regimen had decreased the level of VEGF and P-gp and significantly reduced tumour proliferation (detected by PET/CT images based on 18F-fluorothymidine uptake). Additionally, mifepristone proved to increase the intracerebral concentration of temozolomide. The lower level of MGMT (related to DNA repair in tumours) previously reported for this combined treatment was herein confirmed. After the mifepristone/temozolomide treatment ended, however, the values of VEGF, P-gp and MGMT increased and reached control levels by 14 wks post-treatment. There was also tumour recurrence, as occurred when administering temozolomide alone. On the other hand, temozolomide led to 100% mortality within 26 days after beginning the drug treatment, while mifepristone/temozolomide enabled 70% survival 60-70 days and 30% survived over 100 days, suggesting that mifepristone could possibly act as a chemo-sensitizing agent for temozolomide.